Optimal capital injections and dividends with tax in a risk model in discrete time - Katharina Bata; Hanspeter Schmidli (European Actuarial Journal, 2020)
We consider a risk model in discrete time with dividends and capital injections. The goal is to maximise the value of a dividend strategy. We show that the optimal strategy is of barrier type. That is, all capital above a certain threshold is paid as dividend. A second problem adds tax to the dividends but an injection leads to an exemption from tax. We show that the value function fulfils a Bellman equation. As a special case, we consider the case of premia of size one. In this case we show that the optimal strategy is a two barrier strategy. That is, there is a barrier if a next dividend of size one can be paid without tax and a barrier if the next dividend of size one will be taxed. In both models, we illustrate the findings by de Finetti's example.
Keywords: B30; G42; K30; J10; 510; Discrete risk model; Optimal dividend problem; Capital injections; Tax; Bellman equation; Two barrier strategy; de Finetti model